Computational Insights into the Isomerism of Hexacoordinate Metal–Sarcophagine Complexes: The Relationship between Structure and Stability. Issue 3 (22nd December 2014) - Algarra, Andrés G.
Abstract: The hexacoordinate complexes that the macrobicyclic ligands (NH3 )2 sar 2+ and (NMe3 )2 sar 2+ (sar = 3, 6, 10, 13, 16, 19‐hexaazabicyclo[6.6.6]icosane) form with transition metals such as Co III, Co II and Cu II can adopt several isomeric structures. In this article, we have firstly employed DFT methods to compute the relative stability of their Δ‐ ob 3, Δ‐ ob 2 lel, Δ‐ lel 2 ob and Δ‐ lel 3 isomers, as well as the activation barriers for their interconversion. In agreement with the experimental data, the results show that, in general, the different isomers of the Co III and Co II complexes present similar free energies, whereas the Cu II complexes show a strong tendency towards the lel 3 form. In addition, the interplay between the structure and stability of these species has been studied by combining shape maps with a distortion/interaction energy analysis. In contrast to the geometries close to the ideal octahedron that all the studied Co complexes present, the lel 3 structures of [Cu(NH3 )2 sar] 4+ and [Cu(NMe3 )2 sar] 4+ are better described as trigonal prisms. In such structures the ligand adopts a conformation significantly more stable than in the other isomers, and this drives the formation of lel 3 ‐[Cu(NH3 )2 sar] 4+ and lel 3 ‐[Cu(NMe3 )2 sar] 4+ . Overall, the results show a clear relationship between the stability of a given isomer and its degree of distortion with respect to the ideal octahedron (or trigonal prism), with the latter being ultimately dependent on the transition metal and its radius. Abstract : The relative stability of the isomers of M(NR3 )2 sar 2+ (M = Co III, Co II, Cu II ; R = H, Me; sar = 3, 6, 10, 13, 16, 19‐hexaazabicyclo[6.6.6]icosane) was studied by means of DFT calculations. Further combination of distortion/interaction analysis and shape maps revealed its relationship with the degree of distortion with respect to the ideal octahedron, which is ultimately dictated by the metal.